Penerapan Software Rategain dalam Efektivitas Kerja pad Sales and Marketing Departement di Fame Hotel Sunset Road Legian Kuta Bali - Wiguna, Adhi Karya; Widiatmaja, I Gusti Ngurah; Suarka, Fanny Maharani (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2023)
This research discusses RateGain software in its application at Rate gain software application for effectivity working sales n marketing staffs at Fame Hotel Sunset Road Legian, Kuta, Bali. However, in terms of the quality of work of employees in using the Rategain software, it is not known how effectively the employees work, according to employees of Rategain Dode Hoki Mokarisma said